A new concrete plastic-damage model with an evolutive dilatancy parameter. (15th June 2019) - Poliotti, Mauro; Bairán, Jesús-Miguel
Highlights: A novel evolution law for dilatancy of concrete is developed. Effect of dilatancy in concrete under shear and confinement is investigated. Need of variable dilatancy demonstrated for concrete in shear and confinement. Proposed model suitable for different concrete grades. Proposed model reproduces different failure modes without ad-hoc calibration. Abstract: Typical plastic-damage models for concrete use a constant dilatancy parameter. On problems sensitive to confinement and shear softening, this parameter needs ad hoc calibration to fit experimental observations. This makes the model not objective for general applications. To overcome this issue, in this paper, a constitutive plastic-damage model with evolutive dilatancy is proposed for concrete. The evolution of dilatancy is made dependent on the plastic-damage and stress states. The proposed evolution law is validated by comparison of numerical simulations with available experimental results. The validation includes: concrete specimens under uniaxial compression measuring the free expansion, passively confined concrete specimens with different confining materials, and reinforced concrete panels under in-plane shear. It is concluded that the model accurately reproduces concrete lateral expansion through different nonlinear states. Proper modeling of concrete nonlinear expansion proves essential for capturing the response in a number of situations: softening under high shear stresses, confinement, and ductility assessment.